Easy Way to Prepare Reusable Face Shield for Healthcare Workers - Vijay P Agrawal; Munmun V Agrawal (Journal of Clinical and Biomedical Sciences)
Face shield is one of the parts of personal protection equipment. It is used to protect face which in-cludes eyes, nose, mouth etc. It is mainly used by healthcare workers to protect them from patients body fluids like droplets, secretions etc. In the present scenario of limited resources, we have prepared a reusable face shield from lamination Pouch. Keywords: Face shield, Covid 19, personal protection equipment (PPE)